EFFECT OF COUNSELING BY USING VIDEO MEDIA AND LEAFLETS ON KNOWLEDGE AND ATTITUDE OF BREAST SELF EXAMINATION (BREAST SELF-EXAMINATION) ON STUDENTS AT SMA N 1 WONOSARI KLATENON)ON STUDENTS AT SMA N 1 WONOSARI KLATEN - Winarsih Winarsih; Era Revika; Davina Syafa Nabila (Universitas Karya Husada Semarang, 2024)
Breast cancer is the cancer that most often attacks women in Indonesia (28.7%). Mortality is high in breast cancer sufferers, especially in developing countries, which is known as the practice of Sadari (Self-Examination of Breasts). Profile data from the Klaten Health Service, cases of early detection of breast cancer in 2022 have increased compared to 2021. For the 2021 examination results, there were 643 people, 19 of whom were positive (3%). This research aims to determine the effect of counseling using leaflets and video media on female students' knowledge and attitudes of BSE. This type of research is pre-experimental research. The design used is one group pretest-posttest design. The sample in the research was all 97 female students from SMAN 1 Wonosari. with an accidental sampling technique and the statistical test used was Wilcoxon. Results of analysis there is an influence of counseling using video media and leaflets about BSE on the attitudes of female students at SMAN 1 Wonosari with a p-value of 0.000. The average attitude increased by 100%. Conclusion: It is hoped that the Education Department and the Health Service will collaborate in efforts to prevent breast cancer among women, especially teenagers, in all regional schools by conducting outreach on early detection of breast cancer using BSE using video media and leaflets.